2009
DOI: 10.1159/000209260
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Recurrent Stroke, Other Vascular Events and Dementia after Transient Ischaemic Attack and Stroke

Abstract: The early risk of recurrence after transient ischaemic attack (TIA) or minor stroke is high, ranging from 11% at 7 days in population-based studies, where patients are seen non-urgently, to 3% at 7 days in studies where patients are seen urgently in specialist services. In long-term (up to 10 years) studies of vascular risks after TIA and stroke, the risk of stroke is highest early after the event, and then falls, whereas the risk of coronary events is constant over the follow-up period at around 2% per year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 146 publications
2
62
1
4
Order By: Relevance
“…[7][8][9][10][11]26 Patient characteristics, definition of cognitive impairment, and delay from TIA to assessment of cognition differ widely between studies. Furthermore, cognitive assessment is mostly limited to screening tools such as Mini-Mental State Examination and Montreal Cognitive Assessment, which are not sensitive to mild cognitive deficits after stroke and do not assess specific cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11]26 Patient characteristics, definition of cognitive impairment, and delay from TIA to assessment of cognition differ widely between studies. Furthermore, cognitive assessment is mostly limited to screening tools such as Mini-Mental State Examination and Montreal Cognitive Assessment, which are not sensitive to mild cognitive deficits after stroke and do not assess specific cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…After acute ischaemic stroke (AIS) or transient ischaemic attack (TIA), available data suggest that the risk of recurrent vascular events is considerable [1]. The long-term prognosis is substantially determined by atherothrombotic events in other arterial beds [2].…”
Section: Introductionmentioning
confidence: 99%
“…Transient ischemic attack (TIA), a common subtype of cerebrovascular disease, predicts subsequent vascular events in the near future [1,2,3,4,5,6,7,8,9,10]. Several studies have demonstrated that the duration of an attack, the presence of symptoms upon hospital arrival, neuroimaging results, and the presence of vascular diseases are factors that indicate early stroke in TIA patients [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%